An Approach for Solving Goal Programming Problems using Interval Type-2 Fuzzy Goals - Figueroa-García, Juan Carlos; Patiño-Callejas, Juan Sebastian; Espinosa-Ayala, Krisna Yoel (Ingeniería, 2015)
This paper presents a proposal for solving goal problems involving multiple experts opinions and perceptions. In goal programming problems where no statistical data about their goals exist, the use of information coming from experts becomes the last reliable source. This way, we propose an approach to model this kind of goals using Interval Type-2 fuzzy sets, and a simple method for finding an optimal solution based on previous methods that have been proposed for classical fuzzy sets.